Early Detection of Phytophthora colocasiae causing Leaf Blight Disease of Taro using Nucleic Acid Spot Hybridization Technique - Archana, P. V.; Pravi, V.; Jeeva, M. L. (JOURNAL OF ROOT CROPS, 2017)
Taro (Colocasia esculenta), is the most important edible species of the monocotyledonous family Araceae. Leaf blight caused by Phytophthora colocasiae, a soil born oomycetes, has become a major limiting factor in taro production worldwide including India, resulting in heavy yield losses. Currently available methods for the detection of P. colocasiae includes conventional culture-based morphological approaches and PCR based diagnosis, which entirely depends on laboratory equipment. This study presents an alternative nucleic acid spot hybridization technique with the development of highly specific nucleic acid probes. The developed probes showed good quality, high specificity and optimum sensitivity, thus could be used as an effective diagnostic tools for detection of P. colocasiae species, due to the sequence specificity of the nucleic acid molecule.